PELATIHAN EVALUASI PEMBELAJARAN BAHASA DAN SASTRA INDONESIA UNTUK GURU-GURU MAN SE-JAWA BARAT - Sundusiah, Suci; Mulyati, Yeti; Damaianti, Vismaia S; Rahma, Rosita; Widia, Ida; Saadie, Ma’mur (Dimasatra, 2021)
The general purpose of this Community Service (PkM) activity aim to provide knowledge and training to Indonesian MAN teachers throughout West Java. In particular, this PkM activity aims to improve teacher competence in evaluating Indonesian language and literature learning. This activity is important because the demands of education in the 21st century and the industrial era 4.0 are increasingly complex. This activity uses the lecture method and hands-on practice, which is divided into two sessions. The first session is a presentation that two presenters fill while the second session is a parallel session filled with five presenters. The media used are Zoom Meeting, Google Drive, and so on. The results of this activity indicate an increase in the teacher's ability to understand the material. This can be seen in the results of the pre-test and post-test, which increased by 37.25%. In addition, participants' responses showed very positive results.